Meteorological data from ice-free areas in Yukidori Zawa, Langhovde and Kizahashi Hama, Skarvsnes, and Skallen on Sôya Coast, East Antarctica during January 2017–December 2018 (National Institute of Polar Research, 2021)
Meteorological data recorded by automatic weather stations (AWSs) installed at ice-free areas in the middle of Yukidori Zawa, near the coast of Kizahashi Hama, and at the southern shore of Skallen Ôike during the JARE-58 and 60 (2017–2018) was summarized in tables and figures. Almost 2-year data of air temperature, relative humidity, air pressure, wind conditions, solar radiations including photosynthetically active radiation and ultraviolet radiation, were compiled in 3 text files from each AWS:10-min; 1-hr and daily.